Pemberton's Happy Colony: Reappraising the Reception and Legacy of a Nineteenth-Century Utopia. Issue 3 (2nd September 2017) - Skinner, Robin
Abstract: Drawing from his travels through Britain and Europe, and mindful of the work of other theorists and designers, Robert Pemberton proposed a model settlement based upon a new understanding of society and learning. His project challenged the accepted view of lifestyle and class, how people relate to landscape and their urban environment, the nature of learning and education and contemporary commercial practice. His 1854 design of the "Happy Colony" for a New Zealand site proposed a settlement of 10 communities formed in concentric circles. Each community would include places of learning that comprised a small model farm, manufactories, churches and communal habitations interspersed within a series of circular green belts. Pemberton's proposed settlement was a startling, if somewhat impractical, proposition that attempted to subvert educational, urban, commercial and administrative practice. Despite sustained self-promotion and enthusiastic reception within Robert Owen's circle, Pemberton's work made little impression in his own lifetime. However, since the beginning of the twentieth-century, its impact has increased. Significantly, it influenced Ebenezer Howard's thought on Garden Cities, which has impacted on much subsequent development. The project is now discussed in several disparate fields including education, urban theory, utopian studies and New Zealand studies.